2019
DOI: 10.1139/apnm-2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beetroot juice supplementation on 10-km performance in recreational runners

Abstract: The purpose of this study was to investigate the effects of chronic beetroot juice (BRJ) supplementation on 10-km running performance in recreational runners. In a double-blind, placebo-controlled, crossover-designed study, fourteen male recreational runners (age: 27.8 ± 3.4 y) performed three 10-km running tests at baseline, under the conditions of BRJ supplementation and placebo (PLA). Supplementation was administered for three days, and on the day of the assessments, the ingestion occurred two hours before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The same group also demonstrated that the acute ingestion of 6.2 mmol NO 3 in BRJ improved cycling time trial (TT) performance in 9 male cyclists over 4 (2.8%) and 16.1 km (2.7%) versus a PL (Lansley et al 2011b). Other research groups were able to corroborate the exercise economy/performance findings in trained and recreationally active male subjects (Bond et al 2012;Cermak et al 2012a;Porcelli et al 2015;Whitfield et al 2016;de Castro et al 2019).…”
Section: Early Workmentioning
confidence: 73%
“…The same group also demonstrated that the acute ingestion of 6.2 mmol NO 3 in BRJ improved cycling time trial (TT) performance in 9 male cyclists over 4 (2.8%) and 16.1 km (2.7%) versus a PL (Lansley et al 2011b). Other research groups were able to corroborate the exercise economy/performance findings in trained and recreationally active male subjects (Bond et al 2012;Cermak et al 2012a;Porcelli et al 2015;Whitfield et al 2016;de Castro et al 2019).…”
Section: Early Workmentioning
confidence: 73%
“…The most common form of DN supplementation is beetroot juice concentrate (BJC) [27,58,71,78,[82][83][84]. Other forms of DN supplementation include raw beetroot juice (BJ) [85], encapsulated potassium nitrate (PN) [75,80] and beetroot crystals (BC) [79] or a water solution containing sodium nitrate (SN) [68,81]. All these variables in the supplementation protocol could potentially interfere with the ergogenic effects.…”
Section: Dietary Nitrates Studies Methodologymentioning
confidence: 99%
“…Therefore, even the most considerable TT performance changes observed during cycling ergometry measurements in elite athletes may not be relevant (improvement is lower than SWC + TEM, therefore unclear) in real sports events [103]. Interestingly only 5 of the 13 reviewed studies observed performance improvement after DN supplementation ≥ 1.3% [68,75,81,84,85].…”
Section: The Real Benefit For Elite Athletes?mentioning
confidence: 99%
“…A recent double-blind, placebo-controlled, crossover-designed study measured the effect of BRJ on 10 km performance in recreational runners (n=14) [30]. No significant effect of timetrial performance was observed between placebo and BRJ, however there was a significant difference in the first 5 km (24.3 vs. 24.9 min, p = 0.027).…”
Section: Recreational Exercisers Elite Athletes and Athletic Performentioning
confidence: 99%